1997
DOI: 10.1016/s0010-0277(97)00039-5
|View full text |Cite
|
Sign up to set email alerts
|

Looking for the agent: an investigation into consciousness of action and self-consciousness in schizophrenic patients

Abstract: Looking for the agent: an investigation into consciousness of action and self-consciousness in schizophrenic patients. Cognition, Elsevier, 1997, 65, pp.71-86. Looking for the agent: an investigation into consciousness of action and self-consciousness in schizophrenic patients AbstractThe abilities to attribute an action to its proper agent and to understand its meaning when it is produced by someone else are basic aspects of human social communication. Several psychiatric syndromes, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
273
4
14

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(325 citation statements)
references
References 36 publications
20
273
4
14
Order By: Relevance
“…This simple concept closely resembles models of sensorimotor control, which states that in order to successfully control one's movements one has to be able to predict the immediate consequences of one's movements and confirm these predictions against the actual sensory feedback received from the environment. Importantly, these predictions not only allow humans to maintain and correct on-going movements but also to effectively separate their own actions from the environment (Jeannerod, 2003) and from actions of other agents (Daprati et al, 1997;Jeannerod, 2004). One approach to understanding the mechanisms underlying agency, the central monitoring framework (Frith et al, 2000b), is hence based on the internal model for sensorimotor control proposed by Wolpert et al (Miall and Wolpert, 1996;Wolpert et al, 1995).…”
Section: Agencymentioning
confidence: 99%
See 2 more Smart Citations
“…This simple concept closely resembles models of sensorimotor control, which states that in order to successfully control one's movements one has to be able to predict the immediate consequences of one's movements and confirm these predictions against the actual sensory feedback received from the environment. Importantly, these predictions not only allow humans to maintain and correct on-going movements but also to effectively separate their own actions from the environment (Jeannerod, 2003) and from actions of other agents (Daprati et al, 1997;Jeannerod, 2004). One approach to understanding the mechanisms underlying agency, the central monitoring framework (Frith et al, 2000b), is hence based on the internal model for sensorimotor control proposed by Wolpert et al (Miall and Wolpert, 1996;Wolpert et al, 1995).…”
Section: Agencymentioning
confidence: 99%
“…Similarly, previous investigations of agency were important for the study of bodily selfconsciousness, but were focussed on agency for actions of fingers (Knoblich and Repp, 2009;Repp, 2005Repp, , 2006Repp and Knoblich, 2007), hands (Daprati et al, 1997;Daprati and Sirigu, 2002;Salomon et al, 2011;van den Bos and Jeannerod, 2002), or arms (Fourneret and Jeannerod, 1998;Franck et al, 2001;Nielsen, 1963;Synofzik et al, 2006). As the participants' body position was kept constant (except for actions of finger, hand, or arm, as indicated in Fig.…”
Section: Agencymentioning
confidence: 99%
See 1 more Smart Citation
“…This is also reflected in the schizophrenia literature with respect to speech attribution (Johns et al, 2001, Johns et al, 2006, Stephane et al, 2009) and also with respect to incorrect agency attribution either to external sources or to the self (Daprati, et al, 1997, Fourneret, et al, 2001). In the majority of agency manipulation studies schizophrenia patients showed a tendency similar to that in our study, namely, atendency to attribute what they see to their own agency, despite visual discrepancies (Daprati, et al, 1997, Fourneret, et al, 2001, Haggard et al, 2003, Synofzik et al, 2008. In this regard, we could not detect any difference in attribution style between schizophrenia patients with-and without first-rank symptoms.…”
mentioning
confidence: 93%
“…In contrast, the visual experience of my own body can often be very similar to the Touch and the Body 4 experience of other bodies. Indeed, self-recognition experiments show that people may fail to recognise themselves when shown a screen that switches at random between a video image of their own hand moving, or the hand of an experimenter making a similar movement (Daprati et al, 1997;. In many cases, of course, geometrical perspective, body morphology, or even clothing detail identifies the individual, but the point remains that visual body images are in principle ambiguous between self and other.…”
mentioning
confidence: 99%